An examination of competency required for secretaries in the North-Western Nigerian Colleges of Education - Musa, Muhammad Yahaya (2022)
Competency standards are crucial in the practice of modern-day organisations because it contributes significantly to human resource development, giving organisations a competitive advantage over their competitors. Because of its significance, competency has been a popular research topic. While several researches have taken place, there are significant gaps in secretarial practice in terms of empirical knowledge on secretary competency implementation. This study provides a critical review of the secretarial competencies expected of office technology and management education graduates (OTME), who work as confidential secretaries after graduation from college. The research adopted basic interpretive qualitative design. The objective of the study is “to examine secretaries' industry-required competencies from the perspective of human resource managers and office technology and management lecturers. The study has two (2) research questions and semi-structured interview was used to collect data. OTME minimum standards and OTME lecture time-table were also reviewed for data collection, document review form was used for the document analysis. Semi-structured interview data analysis was done through establishing codes and themes thematically using Nvivo 10 software to facilitate the process. Open coding was employed where themes were established and used to ease data analysis. Findings revealed that practical contact hours should be given more time in OTM curriculum. It was also revealed from findings that shorthand and keyboarding using manual typewriters for instructions should be removed from the OTM curriculum. The results of this study are anticipated to improve the OTME course's instructional design in Nigerian colleges of education by substituting up-to-date courses that comply with current office procedures for those that are out-of-date. It is suggested that the OTME curriculum should be reviewed to eliminate obsolete courses that are no longer relevant to modern secretarial practice. It is recommended that further research be conducted in order to confirm the generalisability of findings